Job Satisfaction and Gender amongst Hotel Sector Managers in the Province of Huelva, Spain - Trillo Rodríguez, María José; Flores Ruiz, David; Ortega Moreno, Mónica (Investigaciones Turísticas, 2025)
An analysis was carried out of the factors that influence job satisfaction in management positions in the hotel sector in the province of Huelva (Spain) from a gender perspective, as well as of the existing gender differences in this sector. To detect gender differences, hypothesis tests for equality of means and proportions were carried out using the Chi-squared and Mann-Whitney U tests, as well as the calculation of Spearman's Rho correlation coefficient to detect correlations between the factors influencing job satisfaction. It is concluded that both gender and sociodemographic differences exist in relation to the characteristics of these jobs. However, there are no significant gender differences regarding the degree of job satisfaction and the factors that determine job satisfaction. Moreover, both motivational and hygiene-related factors play an important role in influencing job satisfaction. The research concludes by providing a number of guidelines that could help reduce the gender differences found in these jobs and, at the same time, improve job satisfaction.